Answer:
3
Explanation:
Subtract
|
x
−
2
|
from both sides of the equation.
|
x
−
1
|
=
3
−
|
x
−
2
|
Reorder
3
and
−
|
x
−
2
|
.
|
x
−
1
|
=
−
|
x
−
2
|
+
3
Remove the absolute value term. This creates a
±
on the right side of the equation because
|
x
|
=
±
x
.
x
−
1
=
±
(
−
|
x
−
2
|
+
3
)
The result consists of both the positive and negative portions of the
±
.
x
−
1
=
−
|
x
−
2
|
+
3
x
−
1
=
−
(
−
|
x
−
2
|
+
3
)
Solve
x
−
1
=
−
|
x
−
2
|
+
3
for
x
.
Tap for more steps...
x
=
3
Solve
x
−
1
=
−
(
−
|
x
−
2
|
+
3
)
for
x
.
Tap for more steps...
x
=
0
Consolidate the solutions.
x
=
3
,
0